Granulocyte Colony-Stimulating Factor (G-CSF): Clinical Use and Oncological Concerns - Pietrzak, Barbara; Patelski, Mikołaj; Klimczak, Adrianna; Kotlarz, Wiktoria; Kamińska, Marta; Kuczma, Matylda; Molenda, Jakub; Czapla, Maciej; Surma, Mateusz; Mikusek, Wiktoria (Quality in Sport, 2026)
Granulocyte colony-stimulating factor is a hematopoietic cytokine mainly produced by myeloid cells. Its primary role is to stimulate and promote neutrophil proliferation, which is commonly used in oncology to prevent myelosuppression often caused by cytotoxic treatment. Growing evidence suggests that its biological activity may extend beyond hematopoiesis and modulate tumor dynamics. Several studies indicate that elevated G-CSF levels and receptor expression are associated with greater aggressiveness and a more unfavourable prognosis. The role of G-CSF in fostering an immunosuppressive microenvironment, supporting metastasis, and promoting tumor growth has become a common area of research. Furthermore, studies have already claimed a higher incidence of secondary malignancies, like acute myeloid leukemia (AML) and myelodysplastic syndrome, among patients receiving G-CSF along with cytotoxic treatment.